Timor-Leste Economic Report, October 2020 : Towards a Sustained Recovery - World Bank (World Bank, Washington, DC, 2020)
This report uses innovative data to investigate the economic impacts of the Coronavirus (COVID-19) pandemic. Timor-Leste is a relatively data-scarce country, which poses a considerable challenge for real-time evidence-based policymaking. Data on overall economic activity is published on an annual basis, household and enterprise surveys are infrequent, and administrative data is often inaccessible or incomplete. Proxy indicators are typically used to gauge recent economic trends. However, the breadth and depth of the shocks induced by Coronavirus (COVID-19) call for the use of novel high frequency data sources to better monitor their economic impacts. Therefore, this report uses data on human mobility, online and social media, transport traffic and satellite imagery. These alternative sources of data provide a valuable complement to existing official statistics by offering additional insights on economic activity. Findings from existing Coronavirus (COVID-19) surveys are also reported.